An optimality criterion to determine areas of endemism - Szumik, Claudia Adriana (2002)
A formal method was developed to determine areas of endemism. The study region is divided into cells, and the number of species that can be considered as endemic is counted for a given set of cells (= area). Thus, the areas with the maximum number of species considered endemic are preferred. This is the first method for the identification of areas of endemism that implements an optimality criterion directly based on considering the aspects of species distribution that are relevant to endemism. The methodis implemented in two computer programs, NDM and VNDM, available from the authors. © 2002 Society of Systematic Biologists.